Performance of the SmartMe&You serious video games for home telemonitoring is related to cognitive status and resting-state electroencephalographic markers in healthy and Parkinson’s disease participants - Claudio Del Percio; Roberta Lizio; Mina De Bartolo; Matteo Carpi; Giuseppe Noce; Susanna Lopez; Antonio Pio Afragola; Federica Fiorentino; Filippo Carducci; Veronica Henao Isaza; Paolo Barone; Arianna Cappiello; et al. (GeroScience, 2026)
Unsupervised serious video games on the SmartMe&You home telemonitoring platform may enable the assessment of cognitive fluctuations in older individuals, with or without cognitive deficits. Here, we tested their validity in cognitively unimpaired older adults (Healthy) and patients with mild cognitive impairment and mild to moderate dementia due to Parkinson’s disease (PDCD). Such validity was assessed using Mini-Mental State Examination (MMSE) scores and resting-state eyes-closed electroencephalography (rsEEG) activity. Clinical, demographic, and rsEEG datasets were collected from 34 healthy and 68 PDCD participants. The SmartMe&You video games included 7 unsupervised cognitive tasks implemented on a commercial tablet. The rsEEG source activities in the individual delta, theta, and alpha frequency bands were estimated using the eLORETA freeware. As novel findings, we showed that game performance: (1) discriminated between healthy participants and PDCD patients, with overall accuracy exceeding 90%; (2) was positively associated with MMSE scores across all participants ( p < 0.00001); and (3) was negatively associated with global rsEEG source activity in the delta and theta frequency bands ( p < 0.00001). These findings suggest that serious videogames of the SmartMe&You home telemonitoring platform were feasible and sensitive to cognitive status across the spectrum from normal aging to Parkinson’s disease-related dementia. This approach provides a scalable, low-cost, and ecologically valid tool for remote cognitive monitoring, with future potential applications in both early detection and longitudinal tracking of cognitive decline.

Associations of IL-17 and TGF-β1 with physical frailty in older adults - Chiara Ceolin; Marina De Rui; Giulia Musso; Silvia Sturani; Adele Ravelli; Cristina Simonato; Franz Villanova; Sabrina Pigozzo; Luca Busetto; Angelo Antonini; Eleonora Fiorenzato; Martina Montagnana; et al. (GeroScience, 2026)
Background Physical frailty is a prevalent geriatric syndrome associated with reduced physiological resilience and adverse outcomes. Beyond classical inflammaging, age-related changes in immune regulation and tissue repair may contribute to frailty pathophysiology. Biomarkers involved in adaptive immune responses and remodeling pathways, such as IL-17 and TGF-β1, may help characterize the inflammatory-regenerative milieu associated with frailty. We therefore investigated the association between circulating immune biomarkers and physical frailty severity in older adults. Methods In this cross-sectional analysis, 167 community-dwelling outpatients aged ≥ 65 years (mean age 75.2 ± 6.4 years; 54.5% women) were classified as robust, pre-frail, or frail according to a phenotype-based frailty score. Circulating levels of TGF-β1, IL-17, IL-6, TNF-α, IL-10, and IFN-γ were measured. Associations with frailty were assessed using ordinal logistic regression, quantile regression, and component-specific logistic models. Results IL-17 concentrations progressively declined with increasing frailty severity (median 9.24 ng/L in robust vs. 4.91 ng/L in frail participants; p = 0.004). In adjusted ordinal models, higher IL-17 levels were independently associated with lower frailty severity (OR = 0.62, 95% CI 0.46–0.84; p = 0.002), with each doubling of IL-17 corresponding to a 28% reduction in frailty odds. Conversely, higher TGF-β1 levels were independently associated with greater frailty severity (OR = 2.33, 95% CI 1.05–5.13; p = 0.036). IL-17 showed consistent associations with physical frailty domains, including slowness (adjusted OR = 0.57), and low physical performance (adjusted OR = 0.68). Similar associations were observed in exploratory analyses restricted to cognitively intact participants. However, formal interaction analyses did not support significant effect modification by cognitive status. In contrast, classical inflammatory markers (IL-6, TNF-α), as well as IFN-γ and IL-10, were not significantly associated with frailty across any of the models. Conclusions Physical frailty was associated with lower IL-17 and higher TGF-β1 levels, suggesting that immune-related pathways beyond classical systemic inflammation may be associated with physical frailty. Rather than reflecting overt systemic inflammation, these findings suggest that biological pathways involved in immune regulation and tissue remodeling may be associated with physical frailty. IL-17 and TGF-β1 may therefore represent potentially informative biomarkers for future investigations of the biological mechanisms underlying resilience and functional decline in aging. Trial registration Not applicable.

Associations of daily step counts with cognitive, clinical, and resting-state electroencephalographic measures in patients with cognitive decline due to Alzheimer’s disease - Matteo Carpi; Mina De Bartolo; Veronica Henao Isaza; Giuseppe Noce; Claudio Del Percio; Susanna Lopez; Filippo Carducci; Roberta Lizio; Antonio Pio Afragola; Burcu Bölükbaş; Federica Fiorentino; Angelo Barone; et al. (GeroScience, 2026)
Sedentary behavior is a recognized and modifiable risk factor for cognitive decline and dementia across neurodegenerative conditions. This study used a smartwatch-based telemonitoring procedure combined with ecological cognitive assessment to examine whether step counts can capture sedentary behavior and its association with cognitive functioning in patients with mild cognitive impairment (ADMCI) and dementia (ADD) due to Alzheimer’s disease. Then, 19 ADD, 28 ADMCI, and 23 cognitively unimpaired older adults (Nold) were consecutively recruited. Participants underwent clinical assessment, resting-state electroencephalography (rsEEG), and neuropsychological testing. They were then monitored at home for approximately one week using Samsung Galaxy Watch 4–6 devices recording step counts (total, purposeful, and incidental) and activity intensity (peak 30-min cadence), together with the unsupervised SmartMe&You-TELEMAIA serious videogame battery administered on a commercial tablet for cognitive assessment. The ADD group showed reduced step counts and lower peak cadence than both ADMCI and Nold participants, whereas rsEEG markers and cognitive measures discriminated the three groups with a graded pattern. Within the AD sample, smartwatch-derived activity metrics were associated with cognitive functioning as assessed by conventional neuropsychological testing and ecological serious videogame performance, but showed limited associations with rsEEG rhythms. EEG delta and alpha rhythms were also more abnormal in the ADD group than in the ADMCI group. Home-based daytime activity monitoring with commercial smartwatches indicated that step volume and intensity are associated with cognitive status in patients with ADMCI and ADD. These findings suggest that smartwatch-derived activity metrics may provide feasible and cost-effective markers of everyday functioning in Alzheimer’s disease. Graphical abstract a Schematic overview of the study design, including resting-state EEG, one-week smartwatch-based activity monitoring, and unsupervised ecological cognitive assessment with the SmartMe&You-TELEMAIA Platform. b Group differences in daily activity metrics across participants with Alzheimer’s disease with dementia (ADD; N = 19), Alzheimer’s disease with mild cognitive impairment (ADMCI; N = 28), and cognitively unimpaired older adults (Nold; N = 23), indicating reduced daily step volume and peak cadence mainly in ADD. c Representative significant associations within the AD clinical sample (ADD + ADMCI; up to N = 47), showing that step metrics were more closely related to cognition (MMSE) and depressive symptom severity (BDI-II) than to resting-state EEG activity, for which only limited associations emerged.

Abnormal periodic and aperiodic resting-state electroencephalographic markers in Lewy body and Alzheimer’s diseases with cognitive decline - Matteo Carpi; Antonio Pio Afragola; Mina De Bartolo; Susanna Lopez; Burcu Bölükbaş; Claudio Del Percio; Veronica Henao Isaza; Roberta Lizio; Giuseppe Noce; Lorenc Barjami; Filippo Carducci; Andrea Soricelli; et al. (GeroScience, 2026)
Lewy body disease (LBD) and Alzheimer’s disease (AD) are the most common causes of cognitive decline and dementia and are associated with characteristic alterations in resting-state electroencephalographic (rsEEG) activity. This multicenter exploratory study investigated periodic and aperiodic rsEEG features in patients with cognitive decline due to Lewy body disease (LBCD) and Alzheimer’s disease (ADCD), compared with cognitively unimpaired older adults (Nold), and examined the clinical relevance of these markers in LBCD. A total of 140 LBCD, 135 ADCD, and 118 Nold datasets from the PDWAVES archive underwent spectral parameterization to decompose rsEEG power spectra (1–30 Hz) into periodic peaks and aperiodic background activity. Both clinical groups showed a significant slowing of the individual alpha frequency (IAF), more pronounced in LBCD, along with reduced periodic alpha and beta power reflected in a lower vigilance index. The aperiodic exponent was elevated in both groups, and the aperiodic offset was also higher in LBCD, suggesting steeper spectral profiles consistent with increased inhibitory cortical tone. Within the LBCD group, poorer cognition was associated with higher low-frequency alpha power, whereas better cognition was predicted by higher high-frequency alpha power. A reduced vigilance index was associated with the presence of visual hallucinations, while no associations emerged for other symptoms. These findings suggest that combined periodic and aperiodic rsEEG features may provide relevant markers of altered vigilance regulation in LBCD. Future studies should evaluate whether these EEG markers can inform targeted interventions, such as neuromodulatory or audiovisual stimulation, to stabilize quiet-vigilance states and improve clinical outcomes. Graphical abstract Panel A shows the spectral parameterization of rsEEG activity into periodic and aperiodic components. Panel B summarizes the main group differences in key rsEEG markers across LBCD, ADCD, and Nold participants. Panel C shows the topographical associations between the vigilance index and cognition and visual hallucinations in LBCD; colors reflect the direction and strength of the associations. For the visual hallucinations map, negative log-odds indicate lower odds of hallucinations for higher vigilance index values, whereas positive log-odds indicate higher odds; values around ± 1.5 correspond approximately to odds ratios of 0.22 and 4.5, respectively. Abbreviations: rsEEG, resting-state electroencephalography; LBCD, cognitive decline due to Lewy body disease; ADCD, cognitive decline due to Alzheimer’s disease; Nold, cognitively unimpaired older adults; IAF, individual alpha frequency; MMSE, Mini-Mental State Examination; p , standardized regression coefficient; log-odds, logistic regression coefficient.

The Role of Cognitive Reserve in Protecting Cerebellar Volumes of Older Adults with mild Cognitive Impairment - Maria Devita; Giulia Debiasi; Mariagiulia Anglani; Chiara Ceolin; Ilaria Mazzonetto; Chiara Begliomini; Simone Cauzzo; Cecilia Raffaelli; Alessandro Lazzarin; Adele Ravelli; Alessandra Bordignon; Marina De Rui; et al. (The Cerebellum, 2024)
The present study aims to investigate the relationship between cerebellar volumes and cognitive reserve in individuals with Mild Cognitive Impairment (MCI). A description of proxies of cerebellar cognitive reserve in terms of different volumes across lobules is also provided. 36 individuals with MCI underwent neuropsychological (MoCA, MMSE, Clock test, CRIq) assessment and neuroimaging acquisition with magnetic resonance imaging at 3 T. Simple linear correlations were applied between cerebellar volumes and cognitive measures. Multiple linear regression models were then used to estimate standardized regression coefficients and 95% confidence intervals. Simple linear correlations between cerebellar lobules volumes and cognitive features highlighted a significant association between CRIq_Working activity and specific motor cerebellar volumes: Left_V (ρ = 0.40, p = 0.02), Right_V (r = 0.42, p = 0.002), Vermis_VIIIb (ρ = 0.47, p = 0.003), Left_X (ρ = -0.46, p = 0.002) and Vermis_X (r = 0.35, p = 0.03). Furthermore, CRIq_Working activity scores correlated with certain cerebellar lobules implicated in cognition: Left_Crus_II, Vermis VIIb, Left_IX. MMSE was associated only with the Right_VIIB volume (r = 0.35, p = 0.02), while Clock Drawing Test scores correlated with both Left_Crus_I and Right_Crus_I (r = -0.42 and r = 0.42, p = 0.02, respectively). This study suggests that a higher cognitive reserve is associated with specific cerebellar lobule volumes and that Working activity may play a predominant role in this association. These findings contribute to the understanding of the relationship between cerebellar volumes and cognitive reserve, highlighting the potential modulatory role of Working activity on cerebellum response to cognitive decline. Graphical Abstract